Serum transaminase level changes in dengue Fever and its correlation with disease severity - Mahmuduzzaman, M; Chowdhury, AS; Ghosh, DK; Kabir, IM; Rahman, MA; Ali, MS (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):349-55. The abstract of this article is available on the PubMed website